PENGARUH GOOD CORPORATE GOVERNANCE (GCG) DAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP NILAI PERUSAHAAN - Rofika Rofika (VALUTA, 2016)
This study aims to examine and emperically prove the influence of Good Corporate Governance (GCG)and Corporate Social Responsibility (CSR) to company value. As the proxies of GCG are institutionalownership, managerial ownership, independent commissioner and the audit quality. The sample of studyis Food and Beverage company listed on Indonesian Stock Exchange periode 2010 – 2012. The samplingdesign of this study is purposive sampling with the final sample 14 company. That so the wholeobservation amounted 42. To test the hypothesis proposed is used multiple regession analysis. The resultof hypothesis testing showed that institutional ownership, independent commissioner, audit quality andCSR statisticly have significant influence to company value. While managerial ownership has notsignificat influence to company value.